Щодо підвищення ефективності оптичних електротехногій в біотехнічних системах - Червінський, Л. С.; Сторожук, Л.О. (Energy and Automation, 2017)
OPTICAL ELEKTROTECHNOLOGY IS WIDELY USED IN ALL SECTORS OF ECONOMYL. Chervinskyi, L. Storozhuk  Topicality.  Currently, the main issue that is becoming more important - a saving that seeks professional methods and technologies for energy efficiency optical radiation. Therefore, finding opportunities to save energy in the process of growing greenhouse plants using energy of optical radiation is a very important practical purpose.Analysis of recent research and publications. The energy of optical radiation in greenhouse production can not be replaced by any other technology or Agrotechnological techniques. But trying to use optical Electrotechnology where it kolkist improves quality, reduces the time of vegetation grown greenhouse production, decreases energy technological process, increase productivity and economically justified.Object is a system biotech greenhouses using optical electrotechnology variable light fields. Feature of the given electrical technologies is that the optical energy radiation is in the process several stages of transformation:The aim - to justify the features that facilitate the introduction of new optical electrotechnologies particular variable light field.Materials and methods. The process of biological exposure area has a number of features.The first feature.The actual method of radiation biological object defines the parameters of alternating light field:The second feature.The subject of the influence of alternating light field is a biological object. On the functional side photo-biological reactions can be divided into actual physiological and destructive-modifying. The first, which is divided into produktostvoryuyuchymy:• energy processes (photosynthesis);• biosynthetic process (chlorophyll biosynthesis);• Information Processes (phototropism, fotomorfohenez, photoperiodicity, photosynthetic reaction fotoadaptatsiya).The third feature.The question of the effectiveness of the radiation, ie light energy to optimize the impact on plants is of great practical importance, which requires wider knowledge of patterns of effects on living organisms. In other words, requires identification of plants as objects of light exposure.The fourth feature.The approach of the criteria is the ultimate in Illumination. In the case of plants - this may be the performance of photosynthesis and phenological indicators of the object.Results and discussion. In practice, technological greenhouses lighting system of rationing 'exposure developed without considering the peculiarities of the plant. Therefore systematization of known results of the impact of variable light conditions at the plant is a major issue in the normalization process practical lighting.Conclusions and prospects.1. The use of variable light irradiation fields greenhouse plants is a promising area of  energy conservation and energy efficiency.2. Traditional scheme irradiation plants is characterized by unilateral action on biological objects povirhnyu.3. The need to develop a systematic approach to energy savings for open biotechnical system, which uses optical electrotechnology. And also solve the problem of dynamic performance optimization of plant photosynthesis.